Potential of meniran extract (Phyllanthus niruri Linn) on the economic value of feed and income over feed cost in Texel sheep - Febriano, Muhammad Galang; Emy Koestanti Sabdoningrum; Pudji Srianto; Sri Hidanah; Soeharsono, Soeharsono; Kadek Rachmawati (Jurnal Agro Veteriner, 2025)
The research was conducted using completely randomized design by divided 24 Texel sheeps into 4 treatments, each treatment consisted of 6 repetitions. The treatment groups consisted of: P0 (sheeps were given CMC-Na 0,5% solution), P1 (given meniran extracts at 5% concentration), P2 (given meniran extracts at 10% concentration) and P3 (given meniran extracts at 20% concentration). Administration of treatment between groups using a syringe (20 ml). The data were analyzed statistically using the Analysis of Variance (ANOVA) and continued with Duncan's test. The economic value of feed is obtained from the feed conversion value multiplied by the feed price, where the feed conversion is obtained from the ratio between the amount of feed consumption and body weight gain. The income over feed cost obtained through the difference between income and total feed costs, where the total feed price is obtained from the cost of Texel sheep feed plus the cost of meniran extract (Phyllanthus niruri Linn). P1 with meniran extract 5% gives the best result. It can be conclude that the addition of 5% meniran extract could reduce the economic value of feed and increase income over feed costs on Texel sheeps.